Character association and path analysis of quantitative traits among marigold (Tagetes sp.) genotypes - POULOSE, BIBIN; PALIWAL, AJAYA; BOHRA, MAMTA; PUNETHA, PARUL; BAHUGUNA, PANKAJ; NAMITA, NAMITA (The Indian Journal of Agricultural Sciences, 2021)
The path-coefficient analysis provides information about direct and indirect effect of other morphological characteristics on flower yield per plant, hence this investigation was undertaken to study the effects of various quantitative traits among marigold (Tagetes sp.) genotypes. The genetic variability and heritability in 21 genotypes of marigold confirmed that there is a colossal difference between the genotypes for yield and other 17 traits. The number of ray florets/ flower showed high heritability (99.95) together with high genetic advance (255.77) followed by fresh weight of flower and yield per plant. The study revealed that the PCV is more in comparison with GCV for all the traits which indicates, the contribution of the environment in the expression of traits. Correlation analysis between yield and yield attributing traits in marigold genotypes revealed high positive correlation of flower yield per plant at both phenotypic and genotypic levels with traits like plant height, plant spread, number of primary branches per plant, stem diameter, number of leaves per plant, fresh weight of flower, flower diameter, number of ray florets per flower and flowering duration. Path analysis revealed that the characters like fresh weight of flower and number of flowers per plant are important characters affecting flower yield since they had high direct positive effect. The magnitude of genetic divergence of marigold collected from four different states of India showed the presence of wide genetic diversity. Characters of maximum association with yield have been identified and a selection programme based on the above traits shall be highly effective in improving flower yield of marigold.